The PDE10A inhibitor MP-10 and haloperidol produce distinct gene expression profiles in the striatum and influence cataleptic behavior in rodents. (December 2015) - Gentzel, Renee C.; Toolan, Dawn; Roberts, Rhonda; Koser, Amy Jo; Kandebo, Monika; Hershey, James; Renger, John J.; Uslaner, Jason; Smith, Sean M.
Abstract: Phosphodiesterase 10A (PDE10A) has garnered attention as a potential therapeutic target for schizophrenia due to its prominent striatal expression and ability to modulate striatal signaling. The present study used the selective PDE10A inhibitor MP-10 and the dopamine D2 antagonist haloperidol to compare effects of PDE10A inhibition and dopamine D2 blockade on striatopallidal (D2) and striatonigral (D1) pathway activation. Our studies confirmed that administration of MP-10 significantly elevates expression of the immediate early genes (IEG) c-fos, egr - 1, and arc in rat striatum. Furthermore, we demonstrated that MP-10 induced egr - 1 expression was distributed evenly between enkephalin-containing D2-neurons and substance P-containing D1-neurons. In contrast, haloperidol (3 mg/kg) selectively activated egr -1 expression in enkephalin neurons. Co-administration of MP-10 and haloperidol (0.5 mg/kg) increased IEG expression to a greater extent than either compound alone. Similarly, in a rat catalepsy assay, administration of haloperidol (0.5 mg/kg) or MP-10 (3–30 mg/kg) did not produce cataleptic behavior when dosed alone, but co-administration of haloperidol with MP-10 (3 and 10 mg/kg) induced cataleptic behaviors. Interestingly, co-administration of haloperidol with a high dose of MP-10 (30 mg/kg) failed to produce cataleptic behavior. These findings are important for understanding the neural circuits involved in catalepsy and suggest that the behavioral effects produced by PDE10A inhibitors may be influenced by concomitant medication and the level of PDE10A inhibition achieved by the dose of the inhibitor. Highlights: MP-10 induces striatal expression of the immediate early genes arc, c- fos, and egr -1. MP-10 egr -1 expression is evenly spread among striatonigral and striatopallidal neurons. Low, but not high, MP-10 doses interact with haloperidol to induce cataleptic behavior.